(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Miniaturization is one of the key trends in medical field. In order to keep up with increasing demand novel manufacturing techniques have to be developed. Here we present an approach of using amplified femtosecond laser to realize both additive and subtractive micro-machining in a single workstation. It allows simplification of fabrication workflow as well as allows to produce more complex microdevices. Example structures, such as macromolecule separator and flow meter are demonstrated. We highlight peculiarities, challenges and opportunities that can be exploited using hybrid manufacturing and how it can be employed in medical field